Bone Metastases and Skeletal Complications: Information and Involvement of Patients with Cancer in the Treatment Pathway - Stefania Gori; Alessandra Fabi; Giuseppe Procopio; Mario Airoldi; Alberto Zambelli; Gaetano Lanzetta; Sergio Bracarda; Jennifer Foglietta; Silvana Leo; Anna Baggi; Jean Marie Franzini; Matteo Valerio; et al. (Oncology and Therapy)
Abstract Introduction Adequate information about patients with bone metastases could increase adherence to treatment and reduce or delay skeletal and dental complications. Limited data are available on patient awareness, the degree of information received, and adherence to specific treatment for bone metastases. Methods ROPI (Rete Oncologica Pazienti Italia) conducted an anonymous survey from 1 February to 31 August 2022 among patients with bone metastases from solid tumors to evaluate their level of information and adherence to specific treatments and dental evaluations. Questionnaires were administered by oncologists or nurses at participating cancer centers. Results Analysis of 351 questionnaires revealed that 75% of patients felt “fairly/well” informed about bone metastases and skeletal complications. The oncologists were the primary source of information. More than 80% of patients reported undergoing specific treatment for bone metastases (denosumab, 48%; zoledronic acid, 46%); 93% of patients received dental evaluations before starting therapy (with dental complications in only 0.3% of patients) and 78% received information about the importance of regular dental checkups. Vitamin D and calcium supplements were taken by 83% of patients. Among patients with skeletal complications (47% of patients), bone radiotherapy was the most frequent (94%). Conclusions Most patients stated that they had received information about bone metastases, skeletal complications, and specific treatments. This could increase awareness and adherence to treatment and potentially reduce or delay skeletal and/or dental complications improving patients’ quality of life and survival.